2022
DOI: 10.3390/nano12142495
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Flexible Pressure Sensor Arrays

Abstract: Flexible pressure sensors that can maintain their pressure sensing ability with arbitrary deformation play an essential role in a wide range of applications, such as aerospace, prosthetics, robotics, healthcare, human–machine interfaces, and electronic skin. Flexible pressure sensors with diverse conversion principles and structural designs have been extensively studied. At present, with the development of 5G and the Internet of Things, there is a huge demand for flexible pressure sensor arrays with high resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 122 publications
0
11
0
Order By: Relevance
“…The results are presented in Figure g–i. Therefore, it is shown that the self-powered pressure sensor developed in this study has potential applications in health and activity monitoring (e.g., gait monitoring) by measuring the pressure distribution in the insole. , …”
Section: Resultsmentioning
confidence: 99%
“…The results are presented in Figure g–i. Therefore, it is shown that the self-powered pressure sensor developed in this study has potential applications in health and activity monitoring (e.g., gait monitoring) by measuring the pressure distribution in the insole. , …”
Section: Resultsmentioning
confidence: 99%
“…Flexible strain/pressure sensors have various fields of application [ 119 ]. We did not intend to review all the relevant works in this subsection.…”
Section: Flexible Strain/pressure Sensorsmentioning
confidence: 99%
“…The basic sensing mechanism of pressure sensors is converting the change of physical pressure into electrical signals, and the transduction can be carried out in different forms, e.g., piezoresistivity, piezoelectricity, triboelectricity and capacitance [ 183 ]. Taking the piezoresistive pressure sensor as an example, it suggests that the applied pressure will change the size of the contact area, thus causing the change of the resistance value [ 184 ].…”
Section: Sensing With Carbon Materialsmentioning
confidence: 99%